Effect of tocotrienol rich fraction (TRF) on muscles reinnervation after sciatic nerve crush injury in rats - Lailanor, Amalia; Yahya, Nurul Alaina; Sanusi, Junedah; Khaza'ai, Huzwah; Che Ramli, Muhammad Danial (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Muscle denervation is a process where muscles lose nerve supply due to neural damage and this may lead to paralysis in human. Muscle denervation is mainly caused by peripheral nerve injuries especially in the lower extremities that resulted in devastating effect on human daily functions and routines. Tocotrienol Rich Fraction (TRF) consist of 75% of tocotrienols have shown potential neuroprotective properties. The objective of this study is to observe motor coordination and histological characteristics on muscles that underwent sciatic nerve crush injury and supplemented with TRF. Methods: A total of 104 Sprague-Dawley rats were divided into four groups; normal group (n=8) with no sciatic nerve crush injury, negative control (n=32) with sciatic nerve crush injury at hindlimb without treatment, positive control (n=32) sciatic nerve crush injury treated with 500 μg/kg/day of methylcobalamin, and experimental group (n=32) of rats that underwent sciatic nerve crush injury and treated with 200 mg/kg/day of TRF. Result: Skeletal muscles which located at hind limb; Soleus Muscle and Extenstor Digitorum Longus Muscle (EDL) muscle have shown an increasing in weight when it is supplemented with TRF 200 mg/kg/day and improved myelin layer of nerve. Conclusion: This study showed that TRF has the potency to improve reinnervation rate and neuron supply in hind muscle.